Percepción social sobre el manejo de los residuos sólidos domiciliarios en zona urbana de Villa Punchana, Maynas 2022 - Paredes Flores, Bertha Arle (2022)
The objective of this work was to describe the social perception about the handling and management of solid waste in the inhabitants of the urban area of Villa Punchana in the year 2022. Due to its approach, it was quantitative, prospective, simple descriptive and non-experimental design. The target population was 7,168 residents, with housing in the area. The sample was also constituted by 83 inhabitants calculated at a confidence level of 90% and p of 0.50, inclusion and exclusion criteria were taken into account, the technique was the survey and the instrument applied was a questionnaire of eighteen questions the same as what happened the validity tests (binomial test) and reliability (Kudder Richardson). The data were analyzed taking into account the objectives and the hypothesis and processed and tabulated through the statistical package SPSS version 23. The results regarding environmental contamination indicated that There are diverse opinions on the part of these residents, indicating mostly that the changes in the environment where they live are not the product of local activity, that these changes are due to air pollution and poor management of solid waste and that they are aware that there is a progressive degradation and pollution of the environment in general. The social perception about the management of household solid waste was regular with 54.2%, in contrast to 12% it was bad and 33.7% good. The social perception regarding the municipal management of solid waste was that 68.7% stated that it is bad, in contrast, 31.3% said that it is good The general social perception on the handling and management of household solid waste in the urban zone of villa Punchana is regular in 54.2%, 26.5% is bad and 19.3% is good.